Critical Thinking Skills and Digital Literacy of High School Students in Science Learning Using E-Learning with STEM Vision - Rahayu, Sarini; Isnaeni, Wiwi; Masturi, Masturi (Universitas Negeri Semarang, 2022)
Critical thinking skills and digital literacy are competencies that students must have in facing the challenges of 21st century learning, including contextual biology learning and a STEM approach. The learning process is accompanied by technological developments so that it needs to be utilized optimally through E-Learning. This study aims to analyze the effect of STEM-Vision E-Learning on digital literacy, critical thinking, and determine teacher and student responses to the application of STEM-Vision E-Learning learning. This study used a quasi-experimental design with a pretest-posttest control group design. The subjects of this study included 60 students in class XI MIPA 4 and 5 as the Experiment class (E-Learning with STEM Vision) and 60 students in XI MIPA 6 and 7 as the control class (Conventional E-Learning). This research was conducted at SMA N 1 Ungaran. The data measured in this study were critical thinking skills, digital literacy, and teacher and student responses to the application of STEM-Vision E-Learning learning. This study uses measuring instruments of observation, interviews, questionnaires, written tests and analyzed using reliability test, validity test, n-gain test. The results showed that in general there was a significant difference in digital literacy between the experimental class and the control class, In addition, there is a significant difference in critical thinking skills between the experimental class and the control class and there is a significant difference in critical thinking skills and digital literacy between the experimental class and the control class. Learning STEM Vision E-Learning can be implemented well, students and teachers give a positive response to learning STEM Vision E-Learning on the material circulation system. Suggestions in this study need a STEM approach between teachers and students so that online learning takes place without obstacles.